Aristophanes’ Dramatic Works and Crisis of Polis World-View - Lytovskaya, Alexandra (Pitannâ lìteraturoznavstva, 2013)
The purpose of the article is analysis of correlation between specifics of composition in Aristophanes’ comedy and fundamental changes of Athenians’ world-view. In the end of V – beginning of IV century B.C. – period of progressive decline of Athens which caused rethinking of new way of interference between world and human being. Using comparative and historical approaches author argues that while tragedy remains restrained by genre canon formed in the epoch of Athens’ flowering, Aristophanes’ comedy with its freedom of contents and representation means is proves to be able to answer demands of new time. The analysis of structure of Aristophanes’ plays reveals tendencies of violation of standard pattern of Greek drama, freedom in arranging traditional dramatic elements as parabasis, agon, part of chorus etc. As a result dramatic action is developed as system of equivalently meaningful episodes. This principle of dramatic composition allows Aristophanes to show complicated interaction between remote aspects of polis’ life such as war, citizenship law, literature, philosophy and private life. Freedom in dramatic structuring includes violation of time and place unity, genre interaction, combining of laughter and seriousness, breaking of theatrical illusion which are signs of folk chronotope and open dramatic form. Research implication. Downfall of Athens and fundamental changes in Athenian’s world-view caused overrun of dramatic tradition. Principles of open form in Aristophanes’ comedies are considered as discovering of new artistic methods to rethink new situation. Consideration of Old Attic Comedy as first example of open form in Europan theatre determines originality of the article.